2016
DOI: 10.1111/bju.13513
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and oncological outcomes of a contemporary radical prostatectomy practice in a UK regional tertiary referral centre

Abstract: This study suggests that the patient profile for RALP in our unit is changing, with increasing proportions of higher stage and more advanced disease being referred and operated on. However, surgical margin outcomes have remained good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…Exploring biopsy specimens, we found a net increase in Gleason scores of 7 and ≥8 as well as significant growth in the percentage of positive biopsies: in 2015, 28% of patients had >50% positive biopsy cores, whereas 17% did in 2010. This is in line with recent studies of mainly open radical prostatectomies from several tertiary referral centers across the United States and Europe . Notably, we observed a significant decrease in Gleason 6 (3 + 3) scores (from 45% to 23%) with a concomitant rise in Gleason 7 (4 + 3) scores (from 7% to 21%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Exploring biopsy specimens, we found a net increase in Gleason scores of 7 and ≥8 as well as significant growth in the percentage of positive biopsies: in 2015, 28% of patients had >50% positive biopsy cores, whereas 17% did in 2010. This is in line with recent studies of mainly open radical prostatectomies from several tertiary referral centers across the United States and Europe . Notably, we observed a significant decrease in Gleason 6 (3 + 3) scores (from 45% to 23%) with a concomitant rise in Gleason 7 (4 + 3) scores (from 7% to 21%).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Silberstein et al reviewed 6624 consecutive PCa patients undergoing radical prostatectomy at the Memorial Sloan Kettering Cancer Center in New York: indeed, a steady increase in high‐risk, locally advanced cases was found as well as a reduction in organ‐confined, low‐risk PCa. In Europe, Gnanapragasam et al recently reported a similar stage migration in England: the Gleason 7 rate increased from 55% to 65% between 2005 and 2015, and the Gleason 9 to 10 rate rose from 1.8% to 5.7%. Finally, Huland and Graefen published their German series and found a net reduction in overtreatment across the last 10 years, with the rate of Gleason 6 (3 + 3) cases dropping from 52.2% to 12.1% …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Consistent with the aforementioned observations, there was increase in the proportion of men with pathological stage T3 disease, consistent with other international series . Despite operating on higher risk patients, PSM rates decreased with time (27.3% to 12.1%, P = 0.0419).…”
Section: Discussionsupporting
confidence: 91%
“…Since the advent of nerve-sparing radical prostatectomy (RP) the goal of the surgical management of prostate cancer is to achieve the 'pentafecta' of undetectable PSA, urinary continence, potency, straightforward postoperative recovery, and negative surgical margins (SMs) [1]. Several studies have reported positive SMs (PSMs) to be an important independent predictor of biochemical recurrence (BCR) [2,3], particularly in locally advanced disease, and rates of PSM remain variable despite improvements in surgical technique and technology [4,5]. elevated PSA levels despite no residual cancer, confounding follow-up and causing concern for both patient and surgeon alike.…”
Section: Introductionmentioning
confidence: 99%